The Art Form of Wedha’s Pop Art Portrait (WPAP) - Angga Kusuma Dawami; Martinus Dwi Marianto; Suwarno Wisetrotomo (IJCAS (International Journal of Creative and Arts Studies), 2021)
Wedha's Pop Art Portrait (WPAP) has become one of the most popular visual arts in Indonesia since Wedha Abdul Rasyid decided on this style in 2010. A decade later, WPAP became part of visual arts in Indonesia, used by many millennial designers, sheltered by the chapter community in regions; Jakarta chapter, Jogjakarta chapter, Surabaya chapter, etc. Visual arts-based on faces is a strong characteristic of WPAP. Only a few have achieved the WPAP form in accordance with the art form that Wedha first brought up. Economic motives became the biggest influence on the change in orientation from WPAP art to commodity. Therefore, the art form in WPAP tends to follow market trends. This paper tries to define the existing art in WPAP, with the formulation of the problem: what is the art form in WPAP in Indonesia? The formal approach to art is an important part of knowing art in WPAP. Through descriptive-analytic, an explanation of the art form in WPAP according to the Wedha’s experience is presented in this paper. The analysis is using an analysis of interactions between members of the WPAP community in several chapters which already have a "chapter" community. The art form in WPAP has almost the same characteristics as Wedha's work in the early appearance of WPAP. Wedha had a past that grapples with artwork; making illustrations, making magazine covers, making comics, and so on. The makers of WPAP in the WPAP community also have an art form in WPAP that is the same in pattern, because it is based on WPAP that was initiated by Wedha at the beginning of its appearance. The art form in WPAP has characteristics in color and line drawing. Bentuk Seni dari Wedha’s Pop Art Portrait (WPAP) Abstrak Wedha's Pop Art Portrait (WPAP) menjadi salah satu seni visual yang banyak digemari sejak Wedha Abdul Rasyid memutuskan gaya ini pada tahun 2010. Satu dekade berikutnya, WPAP menjadi bagian dari seni visual di Indonesia, digunakan oleh banyak desainer milenial, dinaungi oleh komunitas chapter yang ada di wilayah-wilayah; chapter Jakarta, chapter Jogjakarta, chapter Surabaya, dll. Seni visual berbasis pada wajah, menjadi ciri khas yang kuat pada WPAP. Hanya sedikit yang mencapai bentuk WPAP yang sesuai dengan bentuk seni yang Wedha munculkan pertama kali. Motif ekonomi menjadi pengaruh terbesar pada perubahan orientasi dari seni WPAP menjadi komoditi. Sehingga bentuk seni dalam WPAP cenderung untuk mengikuti tren pasar. Tulisan ini mencoba untuk mendefinisikan seni yang ada dalam WPAP, dengan rumusan masalah: Bagaimana bentuk seni dalam WPAP menurut komunitasnya di Indonesia? Pendekatan formal seni menjadi bagian penting untuk mengetahui seni dalam WPAP. Melalui diskriptif-analitik, penjelasan tentang bentuk seni dalam WPAP menurut komunitasnya disajikan dalam tulisan ini. Analisis yang digunakan adalah analisis interaksi antar anggota komunitas WPAP di beberapa chapter yang telah memiliki komunitas “chapter”. Bentuk seni dalam WPAP memiliki ciri khas yang hampir sama dengan karya Wedha pada awal-awal kemunculan WPAP pertama kali. Wedha memiliki masa lalu yang bergulat dengan pekerjaan seni; membuat ilustrasi, membuat cover majalah, membuat komik, dan lain sebagainya. Pembuat WPAP di komunitas WPAP juga memiliki bentuk seni dalam WPAP yang sama secara pola, karena memang berbasis pada WPAP yang dicetuskan oleh Wedha pada awal kemunculannya. Bentuk seni dalam WPAP memiliki ciri khas dalam warna, tarikan garis, pemilihan pallet, konstruksi wajah.